Reifying “river”: Unpacking pluriversal possibilities in rejuvenation surrounding the Adi Ganga of Kolkata - Bhattacharya, Shreyashi; Mukherjee, Jenia; Choudry, Anuradha; Ghosh, Raktima (Frontiers in Water, 2023)
Using the River Adi Ganga as the case study and implementing the historical urban political ecology (HUPE) framework, in this article we demonstrate multiple trends and trajectories that comprise city-river relationships. We explore coeval ontologies framing “river,” “riverine space” and “river rejuvenation” schemes, encapsulating “storylines” through the deployment of multi-modal (qualitative) research methodologies to trace and document plural perceptions on the river that was declared to be “dead”—the pillaged stretch that embodied the construction of the metro pillars. Media journalists and activists' narrative, that this act had slaughtered the river and robbed her of her original flows and services, has crafted a deep imprint on the citizens of Kolkata who consider the river as a stinking sink, offering minimal sewerage facilities to the city. Our paper challenges this linear depiction and weaves together positive moments, events and actions that keep the river flowing—shaping and in turn being shaped by (more-than)human actors across long temporal units and scales. We integrate the numerous agential and stakeholder voices attached to the river, shedding light on various (un)successful attempts to revive the river beyond global conceptualizations of what a “river” should be. We believe that the unfolding of this “pluriverse” will forge sustainable understandings of the river's current challenges and existing opportunities toward a collaborative blueprint through knowledge coproduction, stakeholder mobilization and actions. While our empirical frame of reference focuses on micro-realities surrounding a particular river on a specific urban hydroscape, our theoretical conceptualization framings and methodological applications will have potentials to be implemented at scales.